2021
DOI: 10.3892/etm.2021.10450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the differentiation abilities of bone marrow‑derived mesenchymal stem cells and adipose‑derived mesenchymal stem cells toward nucleus pulposus‑like cells in three‑dimensional culture

Abstract: Nucleus pulposus cell (NPC) transplantation can be a potential therapeutic approach for intervertebral disc degeneration (IDD). However, low cell viability has restricted the therapeutic capacity of NPCs, and sources of natural NPCs are limited. Bone marrow-derived mesenchymal stem cells (BMSCs) and adipose-derived mesenchymal stem cells (ADSCs) can be differentiated toward NPC-like cells. However, it is unknown whether there are differences in the abilities of these two cell types to differentiate into NPC-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Thus, 3D culture with alginate beads combined with TGF-β signaling is required for directly differentiating and reprogramming NHDFs to generate NP-like cells in vitro. Additionally, considering potential targets of sources for cell therapy as described above ( Figure 7 ), induced pluripotent stem cells [ 23 , 24 ], adipose-derived or bone marrow-derived mesenchymal stem cells [ 42 , 43 , 46 ], stem cells-derived cartilage endplate cells [ 44 ], and adipocytes [ 45 ] have been reported. Here, we found that NHDF differentiates into NP-like cells by inducing defined factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 3D culture with alginate beads combined with TGF-β signaling is required for directly differentiating and reprogramming NHDFs to generate NP-like cells in vitro. Additionally, considering potential targets of sources for cell therapy as described above ( Figure 7 ), induced pluripotent stem cells [ 23 , 24 ], adipose-derived or bone marrow-derived mesenchymal stem cells [ 42 , 43 , 46 ], stem cells-derived cartilage endplate cells [ 44 ], and adipocytes [ 45 ] have been reported. Here, we found that NHDF differentiates into NP-like cells by inducing defined factors.…”
Section: Discussionmentioning
confidence: 99%
“…When rat BMSCs and ADMSCs were separately cultured in a three-dimensional culture system and compared with BMSCs in three-dimensional culture, ADMSCs in three-dimensional culture exhibited higher mRNA and protein expression of NP cell marker genes such as HIF1-α, glucose transporter-1, and chondrocytespecific genes such as Sox-9, ACAN, and COL II. These findings indicated that ADMSCs had better ability to differentiate into NP cells in three-dimensional culture [69]. In a study on co-culture of ADMSCs and degenerative NP cells, Han et al [70] found that degenerative NP cells exhibited differential expression of lncRNAs and mRNAs, and subsequently explored the relationship between ADMSCs and NP cells in this co-culture system at the gene expression level.…”
Section: Admscsmentioning
confidence: 98%
“…Cytometry results revealed that adipose-derived stem cells (ADSCs) were positive for CD73, CD105, CD44 and Sca-1 [ 56 ] and negative for CD34, CD11b and CD45 [ 57 ]. NP-like [ 57 ] and adipocyte differentiation can be induced in ADSCs.…”
Section: Characteristic Of Disc Progenitor Cells Compared To Traditio...mentioning
confidence: 99%
“…NP-like [ 57 ] and adipocyte differentiation can be induced in ADSCs. Compared to BMSCs, ADSCs exhibited a higher potential for differentiating into NP-like cells, as shown by both genetic and mRNA analysis [ 56 ]. Staining also revealed the osteogenic and chondrogenic potential of ADSCs [ 58 ].…”
Section: Characteristic Of Disc Progenitor Cells Compared To Traditio...mentioning
confidence: 99%
See 1 more Smart Citation